СОЦИАЛЬНАЯ ОБУСЛОВЛЕННОСТЬ КОННОТАТИВНОГО ЗНАЧЕНИЯ СЛОВА (Филолошки студии, 2019)
Many practical and theoretical problems in the area of lexical connotation are not decided until now, although a lot of publications and works in this field. In this article the connotation is considered as sociopsycholinguistical phenomenon that depends on the functioning the word in the communicative situation. Within such model of connotation we can mark out the sociolinguistical (subsystems) components of connotation. These subsystems components indicate the subsystem the word belongs to. In the article the problems of boundaries fuzziness of subsystem connotations and conditionality of these boundaries are demonstrated on the material of informal, low colloquial and slang Russian words, their marks in dictionaries and their appreciation of native speakers (students).